INFORMAÇÕES GEOLÓGICO-GEOMORFOLÓGICAS COMO SUBSÍDIOS À ANÁLISE AMBIENTAL: O EXEMPLO DA PLANÍCIE COSTEIRA DE CARAVELAS - BAHIA - Andrade, Ana Cláudia da Silva (Boletim Paranaense de Geociências, 2002)
A zona costeira de Caravelas, situada no extremo sul da Bahia, apresenta ricos ecossistemas terrestres e aquáticos, incluindo o complexo recifal dos Abrolhos, considerado o mais importante do Atlântico Sul Ocidental. Visando contribuir para a manutenção da qualidade ambiental desta região, confeccionou-se um mapa geológico-geomorfológico onde foi possível a individualização das seguintes unidades: Tabuleiros, Terraços Arenosos Internos, Terraços Argilosos, Terraços Arenosos Externos, Brejos, Planícies de Maré/ Manguezais e Praias. As características destas unidades e os processos ativos limitam ou condicionam o uso e a ocupação humana, sendo desta forma de importância relevante para o planejamento ambiental. GEOLOGIC-GEOMORPHOLOGICAL INFORMATIONS AS SUBSIDIES FOR ENVIRONMENTAL ANALYSIS: THE EXAMPLE OF CARAVELAS COASTAL PLAIN − BAHIA Extended Abstract The coastal zone of Caravelas, located in the Southern part of Bahia State (figure 1), contains diverse and productive ecological systems, including the Abrolhos coral reefs, considered the most important coral reefs of the South Atlantic Ocean. For these reasons this region presents a great potential for tourism and recreation. This activity competes with industrial projects (paper mills), forestry and fossil fuel exploration. In order to contribute to the regional planning of the region, a geologic-geomorphological map was prepared using satellite images and aerial photo in which the following units were identified (figure 2): Table Lands, Inner Sandy Terraces, Outer Sandy Terraces, Muddy Terraces, Tidal Flats/Mangroves, Freshwater Marshes and Beaches. These units present geologic-geomorphological characteristics, which limit or condition the human activities. Some of these characteristics are listed below: Table Lands: i) sand-clay sediments with moderate permeability; ii) good support capacity; iii) recharge area of subterraneous manancial; iv) ground water situated more than 5-10 meters depth; v) risk of mass movements at headwaters, valley walls and sea cliffs. Inner Sandy Terraces: i) sand sediments with high permeability; ii) good support capacity; iii) recharge area of subterraneous manancial; iv) ground water situated less than 3-4 meters depth. Outer Sandy Terraces: i) sand sediments with high permeability; ii) clay with plastic behaviour under this unit near the Caçumba Island; iii) good support capacity where there is no clay with plastic behaviour under this unit; iv) recharge area of subterraneous manancial; v) ground water situated less than 3 meters depth; vi) areas situated between beach-ridges occasionaly inundated. Muddy Terraces: i) clay sediments moderatly consolidated with low permeability; ii) low support capacity; iii) occasionaly inundated. Tidal Flats/Mangroves: i) clay sediments with plastic behaviour, non-compacted; ii) low support capacity; iii) periodic inundation by tides; iv) important ecosystem. Freshwater Marshes: i) clay sediments with plastic behaviour, low permeability; ii) low support capacity; iii) permanent or sazonal inundated areas; iv) important ecosystem. Beaches: i) erosion and/or accumulation processes along the coastline and areas without significant changes. The knowledge of physical characteristics of the substrate and the active geological processes are very important for environmental planning.